STRATEGI PEMASARAN CITIBANK GLOBAL CONSUMER BANK MELALUI PRODUK CITIBANK EAZYPAY - Nugroho Suhardi (NIM 28198187), 2Dwi
Abstract : < p align=\"justify\">As a newcomer in credit card industry since 1989 in Indonesia, Citibank has been selling Visa and Master Card products. Citibank should also be prepared for coping with tough competition against other banks and financial institutions, which sell credit cards. In the year of 2000, 40% of credit card holders in Indonesia were Citibank Card Center consumers. This position was not achieved easily, but by effort and hard works for quite a long time, and Citibank has been building adequately fundamental infrastructure that consists of credit card operational systems and procedures. Furthermore, the promotion activities have helped educating people especially banking consumers to become Cash less Society, which is a tendency of people not to carry and use cash money unnecessarily for buying or purchasing goods and services, instead they tend to use credit card. Citibank EazyPay is a marketing strategy program applied to a credit card product, which facilitates credit card consumers or card holders in determining the purchase of merchandises, especially from specified or selected merchants, within a defined period and the amount of monthly payment decided by the credit card holders themselves, provided the price or the value of items or goods is within the agreed credit limit by Citibank. The author made an assessment toward this strategy application by Citibank, by performing strategy determination analyses. Analysis for external environment using External Factors Evaluation (EFE) Matrix, and Competitive Profile Matrix (CPM) in order to determine the extent of company preparedness for opportunities and external threats, and the company position among its competitors. For internal environment analysis, Internal Factors Evaluation (EFE) Matrix and Boston Consulting Group (BCG) Analysis, were performed, which summarized and evaluated the company\'s major strengths and weaknesses, and the description of the status of a division among other divisions within the same company. Another analysis was the SWOT (Strength, Weakness, Opportunity and Threat) analysis, in order to determine the extent to which company\'s opportunities and external threats can be balanced with its strengths and weaknesses. In addition,he Grand Strategy analysis was performed for alternative strategy formulation, and the company positioning within one of its Quadrants, by obtaining input from CPM and BCG analyses results. Another analysis was Quantitative Strategic Planning (QSP) Matrix, utilizing input from external and internal environment analyses, which will yield a selected strategy amongst many analyzed alternative strategies. From the analysis results, Citibank has been applying Intensive Strategy to perform Market Penetration, Market Development and Product Development. From the implementation of the strategy represented by Citibank EazyPay products, the strategy has also been consistently applied, which was reflected in Product, Price, Place (Distribution), and Promotion. Based on the aforementioned assessment and analysis, the author proposes some suggestions, especially in developing Credit Card products for different segments.